2020
DOI: 10.5005/jp-journals-10024-2791
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Tobacco Use and its Relation to Oral Precancers and Cancers among Individuals Visiting a Tertiary Hospital in South India

Abstract: Aim:The aim of this study was to evaluate the use of tobacco and its association with oral precancers and cancers. Materials and methods: Medical records of 1,007 individuals were assessed for the patterns of tobacco abuse and the presence of tobaccorelated oral mucosal alterations. Results: This study comprised 1,007 individuals (M:F: 95.4%:4.6%). In the cohort, 60.1% had smoking habit and 56.1% had smokeless habit. Of the bidi smokers, 18.2% developed carcinoma, 14.3% developed leukoplakia, which is statisti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Khan et al reported that OSF associated with smokeless tobacco was most prevalent and that gutkha was the most commonly used smokeless product (26.3%). Khan et al reported an odds ratio of 17.704 (95% CI: 4.85-64.58) for developing OSF with a p-value < 0.001 [14]. These findings were confirmed by Mehrotra et al who showed that gutkha usage was associated with an OR of 10.77 (95% CI: 8.18-14.18) [15].…”
Section: Gutkhamentioning
confidence: 78%
See 2 more Smart Citations
“…Khan et al reported that OSF associated with smokeless tobacco was most prevalent and that gutkha was the most commonly used smokeless product (26.3%). Khan et al reported an odds ratio of 17.704 (95% CI: 4.85-64.58) for developing OSF with a p-value < 0.001 [14]. These findings were confirmed by Mehrotra et al who showed that gutkha usage was associated with an OR of 10.77 (95% CI: 8.18-14.18) [15].…”
Section: Gutkhamentioning
confidence: 78%
“…The three articles that described gutkha usage were from the Indian subcontinent. It appears that its practice is increasing and it is being used as a substitute for other BQ forms [14].…”
Section: Gutkhamentioning
confidence: 99%
See 1 more Smart Citation
“…Tobacco use was associated with the utilisation of dental services more than 3 years earlier, which suggests that older people who smoke spend longer periods of time without visiting a dentist. Khan et al 17 state that tobacco in all forms of consumption is a risk factor for oral cancer, which affects older men with greater frequency.…”
Section: Discussionmentioning
confidence: 99%
“…9,12,13,14,15 Other demographic variables, such as age group and skin colour were factors that influenced the use of dental services independently of the timeframe considered and place of residence, as described in the literature. 3,16,17 The use of Brazilian public dental services is greater among the economically underprivileged population. 18 The most vulnerable population is concentrated in this group, the majority of whom have less schooling and brown or black skin colour.…”
Section: Discussionmentioning
confidence: 99%